2018
DOI: 10.1021/acsinfecdis.8b00041
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling Suggests That Promysalin Alters the Metabolic Flux, Motility, and Iron Regulation in Pseudomonas putida KT2440

Abstract: Promysalin, a secondary metabolite produced by P. putida RW10S1, is a narrow-spectrum antibiotic that targets P. aeruginosa over other Pseudomonas spp. P. putida KT2440, a nonproducing strain, displays increased swarming motility and decreased pyoverdine production in the presence of exogenous promysalin. Herein, proteomic and transcriptomic experiments were used to provide insight about how promysalin elicits responses in PPKT2440 and rationalize its species selectivity. RNA-sequencing results suggest that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
(78 reference statements)
1
14
0
Order By: Relevance
“…This mechanism was validated by a resistance selection assay followed by whole genome sequencing of two resulting mutants, revealing the same single nucleotide point mutation of I206V in Sdh. We had previously described the ability of promysalin to chelate iron, but further transcriptomic studies by our group rationalized the antivirulence activity to also correlate to the inhibition of Sdh . Interestingly, the activity and structure of promysalin is reminiscent to that of siccanin, a fungal Sdh inhibitor that was rediscovered as an antibiotic that specifically inhibits PA . , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism was validated by a resistance selection assay followed by whole genome sequencing of two resulting mutants, revealing the same single nucleotide point mutation of I206V in Sdh. We had previously described the ability of promysalin to chelate iron, but further transcriptomic studies by our group rationalized the antivirulence activity to also correlate to the inhibition of Sdh . Interestingly, the activity and structure of promysalin is reminiscent to that of siccanin, a fungal Sdh inhibitor that was rediscovered as an antibiotic that specifically inhibits PA . , …”
mentioning
confidence: 99%
“…We had previously described the ability of promysalin to chelate iron, 16 but further transcriptomic studies by our group rationalized the antivirulence activity to also correlate to the inhibition of Sdh. 21 Interestingly, the activity and structure of promysalin is reminiscent to that of siccanin, a fungal Sdh inhibitor that was rediscovered as an antibiotic that specifically inhibits PA. 22,23 With the protein target identified, we then sought to use this information to strategically design new analogues based on the structure of Sdh. Both of our target identification experiments indicated that promysalin was interacting in the ubiquinone binding site, which is in line with the mechanism of known Sdh inhibitors.…”
mentioning
confidence: 99%
“…Over the past several years, Wuest and co-workers have developed an exciting medicinal chemistry and chemical biology program around the species-selective agent promysalin 53 (Figure A), which targets the major Gram-negative pathogen Pseudomonas aeruginosa . , The multispecies community found in the root systems of various plants is known as the rhizosphere, , and in this environment, bacteria are known to utilize chemical warfare strategies for colonization and to defend themselves. Pseudomonads are highly prevalent in the rhizosphere, and these bacteria produce an array of secondary metabolites with biological activities that promote survival, including antibiotics, virulence factors, biosurfactants, siderophores (to obtain iron from their environment) .…”
Section: Promysalin: a Species-specific Antibiotic That Targets Succi...mentioning
confidence: 99%
“…Further validation that SdhC was the target of 53 was carried out in vitro and via whole genome sequencing of resistant mutants. These findings demonstrate that targeting the tricarboxylic acid (TCA) cycle could be useful in developing narrow, species-selective antibiotic therapies and warrant additional studies regarding SdhC as an antibiotic target. …”
Section: Promysalin: a Species-specific Antibiotic That Targets Succi...mentioning
confidence: 99%
“…[173] Using transcriptomic profiling, Giglio et al showed that a promysalin-resistant P. aeruginosa strain redistributed metabolic flux (down regulate Entner-Doudoroff pathway) to avoid Sdh and entered an irondeficient environment, adding credence to the hypothesis that promysalin's antibacterial efficacy layed on primary metabolism targeting. [174] Terminal oxidases are essential during aerobic respiration to catalyse oxygen reduction while nitrate reductases are important for anaerobic adaption of human pathogens. Pethe et al [175] reported the discovery of Q203, a class of imidazopyridine amide that targeted M. tuberculosis respiratory cytochrome bc1 complex in aureus.…”
Section: Targeting Bacterial Respirationmentioning
confidence: 99%